Understanding Continuance Intention in E-Wallet Services: Security, Trust, and Technology Factors in Malaysia - Tan Lay Hong; Alia Maisarah Abdul Rasid; Aliah Nasuha Mohd Zawawi; Alice Yiung Ni Ni; Aliya Nafisa Mohd Latif; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
The rapid growth of financial technology has increased the adoption of digital payment systems, with the Touch ’n Go (TNG) e-wallet becoming a leading platform in Malaysia. Understanding the factors driving continued usage is essential for sustaining user engagement and competitiveness. This study examines the influence of perceived security, trust, perceived usefulness, and perceived ease of use on users’ intention to continue using the TNG e-wallet. A quantitative research design was employed using a structured online questionnaire administered to active TNG e-wallet users in Malaysia. Data were collected from 104 respondents and analyzed using descriptive statistics, reliability analysis, correlation analysis, and multiple regression analysis. The findings indicate that all four factors positively influence continuance intention, with trust emerging as the strongest predictor (? = 0.409), followed by perceived ease of use (? = 0.245), perceived usefulness (? = 0.221), and perceived security (? = 0.137). The regression model explained 83.6% of the variance in continuance intention (R² = 0.836). The findings highlight the importance of fostering user trust, strengthening security measures, and enhancing the usability and practical value of digital payment platforms. The study provides practical insights for fintech providers seeking to improve customer retention and long-term engagement in the increasingly competitive e-wallet market.